2021
DOI: 10.2196/29268
|View full text |Cite
|
Sign up to set email alerts
|

Self-Focused and Other-Focused Health Concerns as Predictors of the Uptake of Corona Contact Tracing Apps: Empirical Study

Abstract: Background Corona contact tracing apps are a novel and promising measure to reduce the spread of COVID-19. They can help to balance the need to maintain normal life and economic activities as much as possible while still avoiding exponentially growing case numbers. However, a majority of citizens need to be willing to install such an app for it to be effective. Hence, knowledge about drivers for app uptake is crucial. Objective This study aimed to add t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…The intention, in turn, is assumed to predict actual behavior (Maddux & Rogers, 1983). Empirical results from studies conducted in the context of COVID‐19 for explaining contact tracing mobile app use partly support these assumptions: For instance, higher risk perceptions were related to higher intentions to use the app (Große Deters et al, 2021; Kostka & Habich‐Sobiegalla, 2020). Similarly, believing that one has already had COVID‐19 was related to lower app use intentions.…”
Section: Introductionmentioning
confidence: 95%
“…The intention, in turn, is assumed to predict actual behavior (Maddux & Rogers, 1983). Empirical results from studies conducted in the context of COVID‐19 for explaining contact tracing mobile app use partly support these assumptions: For instance, higher risk perceptions were related to higher intentions to use the app (Große Deters et al, 2021; Kostka & Habich‐Sobiegalla, 2020). Similarly, believing that one has already had COVID‐19 was related to lower app use intentions.…”
Section: Introductionmentioning
confidence: 95%
“…Psychological factors also play a part. Deters et al (2021) explored motivations for adopting contact tracing apps in Germany and Switzerland. They found that personal health concerns played a role in adoption, while the possibility of unknowingly infecting others did not.…”
Section: Cultural Factorsmentioning
confidence: 99%
“…The research offers significant and novel findings based on a fine-grained exploration of users' experiences of contact-tracing apps and mobile government in Kuwait using social media sources. Most research on contact tracing focuses on the design of the technology (Bente et al, 2021;Chuenyindee et al, 2022), privacy and cybersecurity (Azad et al, 2021;Bengio et al, 2020), and concern about the operability of the technology (Deters et al, 2021;Osmanlliu et al, 2021;Parker et al, 2020). Few studies have explored system and service quality simultaneously within an information system model, and most studies overlook cultural and social factors in favor of a focus on technical aspects.…”
Section: Introductionmentioning
confidence: 99%